INVESTIGATION OF THE EFFECT OF FORMALDEHYDE INHALATION ON TXNIP AND NF-ΚB LEVELS IN RAT KIDNEY - E. Acar1; R. Tasdemir; F. Hunc; T. Colak; O. D. Ozsoy; B. Bamac; H. M. Kir (Journal of Animal and Plant Sciences, 2020)
Exposure to excessive formaldehyde (FA) has harmful effects on mammalian tissues. The aim was to investigate levels of oxidative stress in rat kidney due to chronic mild FA exposure. Sixteen female adult albino Wistar rats divided into control and experimental groups. The experimental animals were exposed to FA by inhalation to 10 ppm FA for 12 weeks, subchronic exposure. Kidney tissue Thioredoxin Interacting Protein and Nuclear factor-κB p105 levels were examined by enzyme-linked immunosorbent assay kit. The glutathione, malondialdehyde and advanced oxidation protein products levels were measured with the spectrophotometric methods. Serum albumin, creatinine, and urea concentrations were measured with enzymatic colorimetric assay. Compared to the control group, kidney GSH concentrations were significantly decreased in the FA group (P=0.015), while serum MDA concentration showed a significant increase (P=0.002). There was also a statistically insignificant decrease in tissue TXNIP and MDA and insignificant increase in tissue NF-κB p105 and AOPPs concentrations. Moreover, there was a strong positive correlation between tissue MDA and NF-κB p105 (r=0.841, P=0.001). Formaldehyde appears to cause cellular toxicity through oxidative damage because of disruption to oxidant/antioxidant system homeostasis. Subchronic administration of mild dose FA via inhalation to rats does not affect particular parameters on the apoptotic pathway.
Keywords: Formaldehyde; Thioredoxin-interacting protein; Nuclear factor-κB p105; AOPPs; Oxidative Stress; Kidney